ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN RUMAH TANGGA PETANI KARET DESA BENTENG HARAPAN KECAMATAN MAJE KABUPATEN KAUR - Aulina, Parda Oka; Sriyoto, Sriyoto; Yuliarti, Ellys (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2021)
The purpose of this research is to 1) examine the revenue of rubber farmer households; 2) Analyze the expenditure of rubber farmer households; 3) analyze of income of rubber farmer households; and 4) factor affect the households income of rubber farmers in Benteng Harapan Village, Maje District, Kaur Regency. The study was conducted in October 2019. Methods of Data Analysis using quantative analysis for income of rubber farmers and multiple linear regression Analysis. The research sample of 55 respondents. The results showed that revenue farmer household was IDR 6.026.650/month, household expenditure of IDR 5.084.291/ month, income household was IDR942.359/month. Factors affecting income rubber farmers household are the price of rubber, rubber farming experienced, and side jobs. Farmers are expected to be able to maintain the quality of their latex rubber, that is, not to mix other objects so that it weighs on the scales. In marketing rubber, farmers should always be organized, traders should not try to suppress the buying price of rubber